Relationship of Hand Hygiene with the Contamination of Parasite Student’s Intestine of Madrasah Ibtidaiyah in X Islamic Boarding School Surabaya - Ririn Liandari (UNUSA Press, 2021)
Gastrointestinal infection is the highest cause of morbidity and mortality in developing countries with mortality caused by diarrhea as high as 56%. Parasitic infections spread throughout the world and have been shown to be one of the causes of morbidity and disease in areas that are thought to be beneficial for the growth of intestinal parasitic infections. Giardia lamblia is a parasite that has flagellates that attack mammals, including humans, and is considered the most common cause of diarrhea caused by protozoa around the world. Blastocystis hominis is a parasite that is also common in humans, and infects several animals, such as birds, reptiles and anthropods. The purpose of this study was to see the relationship between hand hygiene and parasitic contamination in students at Islamic Boarding School X in Surabaya. This study was an observational study with a cross sectional research design. This research was conducted at one of the Islamic Boarding Schools in Surabaya. The study sample was Madrasah Ibtidaiyah students who received 10 people who participated 7-13 years. The sampling technique in this study was nonprobabilty sampling. The results of the study obtained Rho Spearman value was p = 0.040. The conclusion is that there is a significant relationship between hand hygiene and intestinal contamination in students' feces at the Islamic Boarding School X in Surabaya. Suggestions that can be given are Islamic Boarding Schools which provide guidance and guidance on clean and healthy life to students, teachers and food managers.